2014
DOI: 10.1371/journal.pone.0085761
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Chloroplast Genomes from Wheat, Barley, Rye and Their Relatives Provides a Detailed Insight into the Evolution of the Triticeae Tribe

Abstract: Using Roche/454 technology, we sequenced the chloroplast genomes of 12 Triticeae species, including bread wheat, barley and rye, as well as the diploid progenitors and relatives of bread wheat Triticum urartu, Aegilops speltoides and Ae. tauschii. Two wild tetraploid taxa, Ae. cylindrica and Ae. geniculata, were also included. Additionally, we incorporated wild Einkorn wheat Triticum boeoticum and its domesticated form T. monococcum and two Hordeum spontaneum (wild barley) genotypes. Chloroplast genomes were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(185 citation statements)
references
References 54 publications
14
159
1
Order By: Relevance
“…Barley, which contains diketone wax but in which there are no reports of a dominant wax inhibitor gene, diverged from wheat 8-12 Mya, suggesting that the inverted duplication event that created Iw occurred after this date (74)(75)(76)(77). The inverted duplication may have been a single event in an ancestral wheat genome lineage or separate later events resulting in convergent evolution in B (Iw1) and D (Iw2) genome species.…”
Section: Discussionmentioning
confidence: 99%
“…Barley, which contains diketone wax but in which there are no reports of a dominant wax inhibitor gene, diverged from wheat 8-12 Mya, suggesting that the inverted duplication event that created Iw occurred after this date (74)(75)(76)(77). The inverted duplication may have been a single event in an ancestral wheat genome lineage or separate later events resulting in convergent evolution in B (Iw1) and D (Iw2) genome species.…”
Section: Discussionmentioning
confidence: 99%
“…42, Supplementary Table 5 and Supplementary Note). In contrast, their hosts-rye and wheat, respectively-had already diverged approximately 4 million years ago 9 . This incongruence in the divergence times of a host and pathogen can be due to host tracking: until a few hundreds of thousands of years ago, wheat and rye were still in the host range of a single forma specialis, and divergence into two distinct formae speciales occurred only relatively recently.…”
Section: Openmentioning
confidence: 99%
“…tritici and B. graminis f. sp. hordei diverged approximately 6 million years ago 4 , whereas their hosts, wheat and barley, respectively, diverged at least 2 million years earlier 9 . An alternative explanation could be a recent host jump from wheat to rye or vice versa, followed by the rapid emergence of barriers to gene flow.…”
Section: Openmentioning
confidence: 99%
“…These studies also showed that Bgh and Bgt became reproductively isolated 6.3 million (±1.1 million) years ago, which is after the divergence of the sister Triticeae species barley and wheat (8 million to 9 million years ago; ref. 19). Estimates of the divergence time of the alternating isolate-specific monomorphic and polymorphic regions in both Bgh and Bgt genomes are >5,000 y, implying that these genome mosaics are the product of rare outbreeding events (by sexual reproduction) followed by frequent asexual (clonal) reproduction, which maintains the haploid genome structure in the respective pathogen populations.…”
mentioning
confidence: 99%